New horizons in arginine metabolism, ageing and chronic disease states. (3rd July 2019) - Mangoni, Arduino A; Rodionov, Roman N; McEvoy, Mark; Zinellu, Angelo; Carru, Ciriaco; Sotgia, Salvatore
Abstract: The elucidation of the metabolic pathways of the amino acid arginine and their role in health and disease have been an intensive focus of basic and clinical research for over a century. The recent advent of robust analytical techniques for biomarker assessment in large population cohorts has allowed the investigation of the pathophysiological role of specific arginine metabolites in key chronic disease states in old age, particularly those characterised by a reduced synthesis of endothelial nitric oxide, with consequent vascular disease and atherosclerosis. Two arginine metabolites have been increasingly studied in regard to their potential role in risk stratification and in the identification of novel therapeutic targets: the methylated arginine asymmetric dimethylarginine (ADMA) and the arginine analogue homoarginine. Higher circulating concentrations of ADMA, a potent inhibitor of nitric oxide synthesis, have been shown to predict adverse cardiovascular outcomes. By contrast, there is emerging evidence that homoarginine might exert cardioprotective effects. This review highlights recent advances in the biological and clinical role of ADMA and homoarginine in cardiovascular disease and other emerging fields, particularly chronic obstructive pulmonary disease, dementia, and depression. It also discusses opportunities for future research directions with the ultimate goal of translating knowledge of arginine metabolism, and its role in health and disease, into the clinical care of older adults.